2010
DOI: 10.1111/j.1524-4725.2010.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Photothermolysis for the Treatment of Surgical Scars

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…12,[19][20][21] Glaich and colleagues 20 used the 1,550-nm fractional laser to treat seven patients with hypopigmented scars on the face, and found 51% to 75% improvement in six of seven patients after two to four treatments. 13 Bimatoprost is a prostaglandin analogue commonly used in the treatment of glaucoma, and its use has been associated with hyperpigmentation of periocular skin. The mechanism of action of fractionated laser resurfacing in hypopigmentation remains elusive, but it is theorized that repopulation of resurfaced tissue with normal melanocytes from surrounding tissue results in increased overall pigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[19][20][21] Glaich and colleagues 20 used the 1,550-nm fractional laser to treat seven patients with hypopigmented scars on the face, and found 51% to 75% improvement in six of seven patients after two to four treatments. 13 Bimatoprost is a prostaglandin analogue commonly used in the treatment of glaucoma, and its use has been associated with hyperpigmentation of periocular skin. The mechanism of action of fractionated laser resurfacing in hypopigmentation remains elusive, but it is theorized that repopulation of resurfaced tissue with normal melanocytes from surrounding tissue results in increased overall pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…9 The fractional laser system produces multiple zones of microscopic thermal injury, or microscopic thermal zones (MTZs), surrounded by viable tissue, that provides intact epidermal and dermal cells to migrate into the zone of damage and produce rapid healing. 9,12,13 Topical immunomodulatory drugs such as calcineurin inhibitors (tacrolimus and pimecrolimus) have been used successfully in the treatment of vitiligo not only because of their antiinflammatory characteristics affecting activation of T cells, but also because a direct interaction between calcineurin inhibitors and keratinocytes creates a favorable milieu for melanocytic growth and migration. 9,12,13 Topical immunomodulatory drugs such as calcineurin inhibitors (tacrolimus and pimecrolimus) have been used successfully in the treatment of vitiligo not only because of their antiinflammatory characteristics affecting activation of T cells, but also because a direct interaction between calcineurin inhibitors and keratinocytes creates a favorable milieu for melanocytic growth and migration.…”
mentioning
confidence: 99%
“…Recently nonablative fractional laser (NAFL) therapy has been suggested as a possible effective treatment option to improve surgical scars 7–10 . Studies also show the positive effect of NAFL therapy on scar texture in grafts after burns, 11 in hypertrophic scars, 12,13 in acne scars 14,15 and in the prevention of scars 16 …”
Section: Introductionmentioning
confidence: 99%
“…A larger follow-up study consisting of 13 patients with postsurgical scars showed that after an average of 3 treatments, half of the patients had greater than 75% improvement. 57 Glaich et al 58 demonstrated 51% to 75% improvement in hypopigmented facial scars in 6 of the 7 treated patients with the 1550-nm Fraxel SR. 58 In a comparison study between the 1550-nm fractionated laser and PDL, Tierney et al 59 showed that the fractionated laser was more effective than PDL for improving the cosmesis of surgical scars. A prospective clinical study looked at 13 adults with Fitzpatrick skin types I to III and facial surgical scars with a postoperative duration longer than 6 months.…”
Section: Laser Therapymentioning
confidence: 99%